(untitled) (Baghdad Science Journal, 2024)
Location privacy protection has drawn increasing attention with the popularity of location-based services. This study proposes a context-aware location privacy protection method (CA-LP). CA-LP evaluates users’ location privacy needs by mining their historical trajectories and estimating the privacy leakage degree of locations. Experiments compare CA-LP with other methods on metrics like privacy protection level, quality of service, privacy leakage risk, information loss, and average anonymous time. Results demonstrate CA-LP provides better privacy protection and service quality when considering all factors. CA-LP shows extensive practical value in location sharing applications.